Dingo Howls: The Content and Efficacy of a Long-Range Vocal Signal - Déaux, Éloïse C.; Clarke, Jennifer A.; Charrier, Isabelle (Ethology, 2016)
International audience Signals are shaped through selective pressures impacting their information content (i.e. ‘what’ is conveyed) and their efficacy (i.e. ‘how’ is it conveyed). In the case of long-range communication, a signal's structure should both convey information and allow for detection and discrimination despite the effects of environmental variability during propagation. Canid howls are an ideal example of a long-range communication signal, although research has mostly focused on the relationships between howls’ acoustic characteristics and their potential information content in wolves, Canis lupus spp., and coyotes, Canis latrans. In this study, we quantified these relationships in another canid, the dingo, Canis familiaris dingo, to determine how their howls compare to that of other wild canids. We found that dingoes’ howls are individually distinctive and may convey gender cues. Playback experiments indicate that dingoes can perform class-level recognition of familiar and unfamiliar individuals on the basis of vocalizations alone. These results mirror findings for other wild canids such as wolves and coyotes. Lastly, propagation experiments demonstrate that this signal's structure can permit long-distance detectability and discriminability. We discuss our results in relation to the putative functions of canid howls and propose avenues for future research.